Distance recorder / Mohd Haris Md Khir and Mohd Asri Osman - Md Khir, Mohd Haris; Osman, Mohd Asri (1990)
Distance travelled "by any form of transport which relies on a wheel, is most easily measured "by noting the number of revolutions of a wheel as a vehicles moves along and multiplying that number "by the circumference of the wheel. This project describes a means of electronically measuring, calibrating and displaying the distance travelled "by a wheel. A golf trolley wheel can be used in the prototype but the principle of operation could be applied to any application where distance measurement using a wheel is required. Golfers among the readership will appreciate the important of knowing, during practice, how far a ball has been hit, in order to calculate the distance travelled. Furthermore, realising that measuring a distance travelled by using an electronics equipment is really important for us besides accuracy and less mechanical movement, this types of equipment is invented and is called a DISTANCE RECORDER.